The investigation of fracture characteristics and process optimization of low-cycle fatigue cropping by using an AET-based multi-sensor system - Ren, Yujian (2023)
Low-cycle fatigue cropping (LCFC) is a new method for metal bar separation, which solves the problems such as high active load and energy waste in traditional separate methods. A key issue for LCFC is to achieve high cropping efficiency and good cross-section quality simultaneously. To solve this problem, a novel multi-sensor LCFC system is established to investigate the fracture characteristics of the 16 Mn notched metal bar. In an acoustic emission technique (AET) parameter, the ratio of rise time to amplitude (RA) is used as the control variable for optimization. A 3D microscopy is used to evaluate cross-section quality. Results showed that loading frequency has a big influence on the cross-section quality and the optimal loading frequency is determined. The shear failure model and tensile failure model dominate the crack propagation stage, and the tensile failure model causes poor cross-section quality. RA reflects the failure model change well. An RA-based control scheme is proven to improve the cross-section quality effectively. Combined with cropping time, a suitable RA value is determined.